PROBLEMATIKA PENDIDIKAN AGAMA DI SEKOLAH UMUM - Daulay, Haidar Putra; Dahlan, Zaini; Sabri, Ali; Fasya, Amalia (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2020)
Every student's behavior, consciously or not, is always colored by values ​​that come from the concept of religion he believes in, and always tries to instill these religious values ​​in order to live in himself and others. Through religious education it is hoped that it can encourage students to obey their religious teachings in their daily life and make religion the ethical and moral foundation in their personal, family, community, national and state life. The problems of Islamic religious education in public schools seem to be placed in second place when compared to other subjects. Most of the students do not pay attention to focus on studying Islamic religious education. This problem is none other than the fundamental cause because Islamic religious education does not include lessons at the UN, student behavior is not a measure of starting only based on cognitive, limited hours of Islamic religious education in schools.